SELF-MEDICATION PRACTICE AMONG FIRST YEAR MEDICAL STUDENTS IN UNIVERSITY COLLEGE OF MEDICINE AND DENTISTRY, UNIVERSITY OF LAHORE - Siddique, Ayesha; Mahmood, Hina; Mukhtar, Sara; Leghari, Qurrat ul-ain; Saleem, Shamaila; Nasreen, Maimoona (Pakistan Journal of Physiology, 2015)
Self-medication is the use of medicines by individuals themselves for the treatment of self-diagnosed ailments/conditions. The objective of this study was to assess the pattern of self-medication practice among the 1st year MBBS and BDS students of University College of Medicine and Dentistry (UMCD), Lahore. Methods: A cross-sectional questionnaire based study was conducted amongst 1st year medical students and were selected according to inclusion and exclusion criteria. A structured questionnaire was administered. Purpose of the study was explained to students and confidentiality was ensured. Results: Seventy-four percent of the students practiced self-medication and 26% did not. It was observed that antibiotics (42%) were amongst the commonest drugs used followed by cough suppressants (20%). Most students (62%) reported to use self-medication to save time. Sixty-five percent reported that they recovered completely by self-medication, 21% had other problems, 10% had prolonged morbidity and 4% developed complications. Conclusion: Self-medication is widely practiced among medical students of UCMD, Lahore.